Stabilization and savings funds for nonrenewable resources : experience and fiscal policy implications - Davis, Jeffrey...[et al] (IMF WashingtonUS, 2001)
Examines whether funds can help countries pursue good macroeconomic and especially fiscal policies and consequent design issues.